Active conditioning of ASDEX Upgrade tungsten plasma-facing components and discharge enhancement through boron and boron nitride particulate injection. (14th October 2019) - Lunsford, R.; Rohde, V.; Bortolon, A.; Dux, R.; Herrmann, A.; Kallenbach, A.; McDermott, R.M.; David, P.; Drenik, A.; Laggner, F.; Maingi, R.; Mansfield, D. K.; et al.
Abstract: The injection of boron (B) and boron nitride (BN) powders into ASDEX Upgrade H-mode discharges have demonstrated effective control of tungsten influx in low density/collisionality operational regimes, similar to conventional boronization methods. Sub-mm powder particles are gravitationally accelerated into the upper edge of a lower single null H-mode plasma with a boundary shape roughly conforming to the shape of the poloidal midplane limiters. Visible spectroscopy measurements at one of the outer limiter showed increases in both B and N signal levels, as well as elevated B levels in the divertor, and an increase in total radiated power by greater than a factor of two during BN injection. Globally the BN injection improved energy confinement by 10%–20%, associated with improvements in pedestal performance similar to gaseous N injection. Following conditioning discharges with B powder injection, three low gas-fueling discharges with magnetic perturbations for ELM suppression were successfully conducted. These first results suggest that the application of B containing powders can be used to both improve plasma performance in real-time, and to improve overall wall conditions for subsequent discharges.